STUDY THE ANTIOXIDANT EFFECT OF TOMATO EXTRACT IN OXIDATIVE STRESSED RATS. - Haider H. Humaish (Basrah Journal of Veterinary Research)
Tomato, is today the most popular garden vegetable in worldwide, because of its high consumption. Tomato contain a variety of phytochemical , such as lycopene , flavonoids, glycosides and other chemical constituents that have been beneficial protective effect. The present study carried out to evaluate the effect of two different doses (2 mg/kg BWand 4 mg/kg BW) of tomato extract against hydrogen peroxide-induced oxidative stress in albino rats. Thirty two adult male albino rats randomly divided into four equal groups were used in this study, the results revealed that administration of 0.75% H2O2 in drinking water (groupI) produced significant decline of antioxidant enzymes ( superoxide dismutase (SOD) , glutathione (GSH), catalase (CAT) ) and serum albumin concentration , with significant elevation of lipid peroxidation rate by estimation of malondialdehyde (MDA) and peroxynitrite radical (ONOO). Also, H2O2 caused significant increase in serum concentration of alanine amino transferase (ALT), aspartate amino transferase (AST), alkaline phosphatase (ALP), and bilirubin . On the other hand the animals treated with H2O2 plus 4 mg/kg BW of tomato extract (groupIII) showed significant increase of SOD, GSH, CATand albumin with significant reduction of MDA ,ONOO, ALT, AST, ALP, and bilirubin comparing with control group. Depending on the above oxidant and antioxidant markers, it seems that 4 mg/kg BW. of tomato extract exert beneficial action protect against H2O2 induced oxidative stress in rats.